2006
DOI: 10.1381/096089206778392149
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Leptin, Resistin, and Adiponectin in the White Adipose Tissue of Obese Patients with Non-Alcoholic Fatty Liver Disease and Insulin Resistance

Abstract: Obese patients with insulin resistance have decreased serum adiponectin and increased serum resistin. Additionally, adiponectin gene expression is also decreased in the adipose tissue of these patients. This low level of adiponectin expression may predispose patients to the progressive form of NAFLD or NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 30 publications
4
46
2
Order By: Relevance
“…This finding is in line with other studies that showed that the increasing maternal BMI was also associated with an increased emergency CS delivery rate, which was 1.30 and 1.83 times greater for overweight and obese women compared to normal BMI women 11 . The pathophysiological reason that has been postulated to be behind the increased caesarean-section delivery rates is that the increased BMI, due to the adipose tissue being hormonally active, may predispose women to a reduced response to induced labour because of altered metabolic status when overweight or obese 21,22 . Moreover, it is not impossible that some of the alleged effect on the increased CS delivery rates could be attributed to the more frequent deconditioning in women with a high BMI 23 .…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in line with other studies that showed that the increasing maternal BMI was also associated with an increased emergency CS delivery rate, which was 1.30 and 1.83 times greater for overweight and obese women compared to normal BMI women 11 . The pathophysiological reason that has been postulated to be behind the increased caesarean-section delivery rates is that the increased BMI, due to the adipose tissue being hormonally active, may predispose women to a reduced response to induced labour because of altered metabolic status when overweight or obese 21,22 . Moreover, it is not impossible that some of the alleged effect on the increased CS delivery rates could be attributed to the more frequent deconditioning in women with a high BMI 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Low resistin was negatively correlated with intrahepatic fat content, although this did not reach statistical significance [46] . A third study demonstrated unaltered resistin expression in visceral adipose tissue of patients undergoing bariatric surgery while serum resistin was increased in NASH patients with IR [47] . Interestingly, re-sistin expression in liver tissue of patients suffering from alcohol-induced liver disease or NASH was increased and correlated with inflammatory cell infiltration [48] .…”
Section: Adipokines Are Involved In the Development Of Nashmentioning
confidence: 94%
“…34 In fact, growing evidence indicates that NASH is a consequence of disturbances in the signaling pathways originating from cytokines and adipokines, which can directly or indirectly (through IR) influence its pathogenesis or progression. [35][36][37] Unfortunately, molecular pathways linking adipokines with their nuclear and cytoplasmic targets are largely unknown, so the profiling of these networks awaits the characterizations of corresponding pathways. This study is a step in that direction, because many phosphorylation events differentiating progressive and non-progressive forms of NAFLD also affect adipokine production and signaling.…”
Section: Discussionmentioning
confidence: 99%